Positive Parenting Program to Promote Child Development Among Children 1 to 3 Years Old: A Quasi-Experimental Research - Truong Hoang Viet; Sutham Nanthamongkolchai; Chokchai Munsawaengsub; Supachai Pitikultang (SAGE Publishing, 2022)
Introduction: Child development receives lack of concern and the role of parents in promoting child development is not frequently mentioned in Vietnam. This study aimed to examine the effectiveness of Positive Parenting Program to Promote Child Development on maternal knowledge and practice and development of children aged 1 to 3 years. Methods: This is a quasi-experimental study conducted in Nha Trang city, Vietnam. There are a total of 60 mothers whose children were identified as suspected developmental delayed participated in the study. There were 30 mothers who attended the program as experimental group and 30 mothers who joined the study as comparison group. Ages and Stages Questionnaires, Third Edition (ASQ-3) were applied to assess the child development. Descriptive analysis and paired and independent-samples t -test were applied to examine the research objectives. Results: The findings suggested that after the program implementation, the maternal knowledge of child development and child development of the experimental group were significantly higher than pre-program and the improvements of these variables were better than the comparison group ( P  < .05) while the maternal practice to promote child development was significantly better only within the experimental group. Conclusions: The program was effective in improving several maternal outcomes and child development. The study recommends applying the Positive Parenting Program to Promote Child Development to enhance mother's knowledge of child development and child development.